Resin handicraft and preparation process thereof
By using raw materials such as unsaturated polyester resin, peanut oil and hydrophobically modified carbon nanotubes in resin crafts, and combining ultraviolet curing technology of modified micro-nanocellulose with epoxy silane coupling agent, the porosity problem in resin crafts is solved. Improves apparent quality and durability, achieving more efficient air hole reduction and dust protection.
Patent Information
- Application Number
- CN202411494458.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
AI Technical Summary
Existing resin crafts are prone to bubbles during the stirring process, resulting in residual pores during vacuum evacuation, affecting the appearance quality, and the pores caused by uneven fluidity are difficult to completely eliminate, affecting the beauty and durability of the product.
Using raw materials such as unsaturated polyester resin, fillers, peanut oil, defoaming agents and hydrophobic modified carbon nanotubes, the flexibility and adhesion are increased by adjusting viscosity and fluidity, combined with the preparation of hydrophobic modified carbon nanotubes and epoxy The use of silane coupling agent modified micro-nanocellulose improves the flowability and dispersion of the resin, reduces the generation of pores, and forms a dense coating by curing ultraviolet light.
It significantly reduces the number of surface pores of resin crafts, improves apparent quality and impact resistance, enhances durability and dustproof effect, and extends service life.
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_10
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin handicraft preparation, and more specifically, to a resin handicraft and a preparation process thereof. Background Art
[0002] Resin handicrafts are made of unsaturated polyester resin as the main raw material. They are cast into molds to make various beautiful and lifelike figures, animals, insects, birds, beasts and landscapes, etc. They can also be made into various simulation effects, such as anti-copper, imitation gold, imitation silver, imitation crystal, imitation agate, imitation marble, imitation white marble, imitation mahogany and other resin handicrafts.
[0003] The general processing technology of resin handicrafts on the market is: mix unsaturated polyester resin and filler in a certain proportion, stir thoroughly to obtain slurry for use, add appropriate amount of curing agent, stir evenly and put into mold, perform vacuum and slurry shaking process according to product requirements, demold after molding to obtain preliminary handicrafts, then carry out embryo repair and bottom grinding on the preliminary handicrafts, and finally spray a layer of ink to obtain the finished resin handicraft.
[0004] During the mixing process of unsaturated resin and filler, air may be mixed in to form bubbles. In addition, the uneven flow of unsaturated resin may also cause air entrapment. If these bubbles are not effectively removed during the vacuum process, pores will form in the handicraft, affecting the appearance quality of the resin handicraft.
[0005] In view of the above-mentioned related technologies, the inventors found that it is urgent to provide a resin handicraft with less surface pores and high apparent quality after curing. Summary of the invention
[0006] In order to reduce the number of pores on the surface of a resin handicraft and improve its surface quality, the present application provides a resin handicraft and a preparation process thereof.
[0007] In the first aspect, the present application provides a resin handicraft, which adopts the following technical solution: A resin handicraft comprises the following raw materials in parts by weight: 100 parts of unsaturated polyester resin, 0-1300 parts of filler, 1-3 parts of peanut oil, 0.5-3 parts of curing agent, 0.3-3 parts of defoaming agent, 0.5-1.5 parts of flame retardant, 0.5-1 parts of accelerator and 0.1-1.5 parts of antioxidant.
[0008] By adopting the above technical scheme, unsaturated polyester resin has the advantages of low relative density, high tensile strength, good rigidity, rich resilience, flexibility, excellent weather resistance, etc.; it can be used alone, or filled with reinforcing agents or fillers to be processed into various products, and can also be colored in various colors; it can be used at room temperature or high temperature, and has a wide range of uses. With the increasing development of various molding and processing methods, it has been more and more widely used in industry, construction, transportation and other departments. The requirements of green environmental protection, good health, and saving forest resources have prompted many researchers to combine the characteristics of unsaturated polyester resin to develop wood substitute materials with excellent comprehensive performance, so that it can be successfully applied to various industries and become a major direction of composite material research and development.
[0009] Unsaturated polyester resin is used as the main material of handicrafts. It can be formed at room temperature. After curing, it can form an insoluble and infusible high molecular network polymer with high mechanical strength, making the handicrafts more durable. Unsaturated polyester resin has excellent acid and alkali corrosion resistance, low surface roughness, good electrical insulation, and is suitable for handicrafts that need to withstand a certain voltage. It also has good light transparency and light aging resistance, so that the handicrafts can still maintain their original color and transparency under long-term light exposure, and are not prone to aging and discoloration, extending the service life. It is moderately priced, has high production efficiency, and has a high cost-effectiveness ratio. Peanut oil is added to unsaturated polyester resin, filler and other raw materials. Peanut oil has certain lubricity and flexibility. It can improve the flexibility of the material, make the unsaturated polyester resin more conformable to the shape of the mold when filling the mold, reduce the pores caused by poor resin fluidity or uneven filling, and make the handicraft more durable and not easy to break. Secondly, the natural antioxidants in peanut oil help to resist the influence of external environmental factors on the resin, extend the service life of the resin, and to a certain extent prevent the resin from producing pores due to aging or insufficient chemical reaction. Moreover, peanut oil also has a certain adhesion, which can enhance the adhesion between the unsaturated polyester resin and the mold. During the vacuuming process, this adhesion helps the resin to fit the mold surface more closely, reduce the possibility of air entrapment, thereby reducing the generation of pores and improving the appearance quality.
[0010] Optionally, 1-2 parts by weight of dipentaerythritol hexaacrylate and 0.5-1 parts by weight of epoxy polyacrylate are further added to the resin craft.
[0011] By adopting the above technical scheme, dipentaerythritol hexaacrylate has multiple acrylate groups, and it is a low-viscosity monomer. After being added, it can play a role in diluting the unsaturated polyester resin, thereby reducing the viscosity of the system, increasing fluidity, and reducing the generation of bubbles. In addition, the acrylate group in the dipentaerythritol hexaacrylate has a high reactivity, so it can copolymerize with the unsaturated bonds in the unsaturated polyester resin, thereby changing the molecular structure of the unsaturated polyester resin, thereby changing its fluidity; the epoxy group in the epoxy polyacrylate has a high reactivity, and can chemically react with certain groups in the unsaturated polyester resin, thereby changing the molecular structure of the resin, thereby affecting its viscosity and fluidity. In addition, the polyacrylate itself also has good flexibility and fluidity, which helps to improve the fluidity of the unsaturated polyester resin, making the unsaturated polyester resin easier to flow and fill into the inner wall of the mold, reducing the retention of voids and the generation of pores.
[0012] Optionally, the filler is hydrophobically modified carbon nanotubes.
[0013] By adopting the above technical scheme, carbon nanotubes are a one-dimensional tubular nanomaterial with high aspect ratio, high strength, low density and good conductivity, and have excellent mechanical properties, electrical and optical properties, especially outstanding tensile modulus and tensile strength. The compatibility of hydrophobically modified carbon nanotubes with unsaturated polyester resin is improved, and they can be evenly dispersed in the unsaturated polyester resin, which promotes the plastic deformation of the matrix in the crack initiation and expansion stages, so that a large amount of impact energy is dissipated, and therefore has ultra-high fracture toughness. Moreover, the addition of carbon nanotubes can form a network structure, thereby improving its anti-static effect and reducing dust accumulation. In addition, the hydrophobic modification of carbon nanotubes further enhances the ability to prevent dust accumulation.
[0014] Optionally, the preparation method of the hydrophobically modified carbon nanotubes is as follows: dispersing carbon nanotubes in an acetone solution, adding 2,4-toluene diisocyanate, stirring for 8-10 hours, filtering, and vacuum drying to obtain pretreated carbon nanotubes; The pretreated carbon nanotubes are placed in a tetraethyl orthosilicate solution, ammonia water and ethanol are added, stirred at 60-65° C. for 3-5 hours, aged, and then dried at 190-200° C. for 2-3 hours.
[0015] By adopting the above technical scheme, 2,4-toluene diisocyanate (TDI) contains isocyanate groups, which can react chemically with functional groups on the surface of carbon nanotubes, such as hydroxyl groups and carboxyl groups, to form covalent bonds, thereby firmly connecting TDI molecules to the surface of carbon nanotubes. TDI molecules themselves have certain hydrophobicity, thereby significantly reducing the surface energy of carbon nanotubes, increasing their stability, and improving the dispersibility of carbon nanotubes in unsaturated polyester resins; then, tetraethyl orthosilicate is used to in-situ generate nano-silicon dioxide on carbon nanotubes, and silicon dioxide is loaded on the surface of carbon nanotubes to reduce The surface of the carbon nanotubes is exposed, the interaction between the carbon nanotubes is weakened, and the agglomeration of silica is improved. The synergistic effect of the two makes the filler have better dispersibility and enhances the interaction between the filler and the unsaturated polyester resin. At the same time, the carbon nanotubes have a one-dimensional structure, and the unsaturated polyester resin molecular chain can be entangled with the carbon nanotubes, which hinders the crack propagation during the stress process. Moreover, the carbon nanotubes with a high aspect ratio can bridge each other to form a strong physical cross-linking network between the fillers, thereby improving the impact resistance and tensile resistance of the resin handicrafts, and enhancing the drop resistance and crack resistance.
[0016] Optionally, the mass ratio of the carbon nanotubes, 2,4-toluene diisocyanate and tetraethyl orthosilicate is 1:2-3:1-1.5.
[0017] By adopting the above technical scheme, raw materials such as carbon nanotubes are mixed with appropriate raw materials to prepare hydrophobic modified carbon nanotubes, which can weaken the entanglement of carbon nanotubes, increase their reaction activity, and improve the mechanical strength of carbon nanotubes.
[0018] Optionally, the promoter is at least one of cobalt naphthenate, dimethylaniline, cobalt naphthenate and cobalt octoate; The curing agent is at least one of methyl ethyl ketone peroxide, cyclohexanone peroxide, hydrogen peroxide, peroxydicarbonate and benzoyl peroxide; The flame retardant is selected from at least one of sodium hexametaphosphate, ammonium polyphosphate, ammonium dihydrogen phosphate, diphenyl xylene phosphate, trisnonyl phosphite, triisopropyl phosphate, trimethyl phosphonate, dimethyl methylphosphonate, melamine, melamine cyanuric acid, and melamine phosphate; The defoaming agent is selected from at least one of polydimethylsiloxane, tributyl phosphate, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether and polyacrylamide; The antioxidant is selected from at least one of N,N-diphenyl-p-phenylenediamine, 2-thiol benzoimidazole, 2,6-di-tert-butyl-4-methylphenol, triphenyl phosphite and tributyl sulfite.
[0019] By adopting the above technical scheme, the accelerator can induce the decomposition of the curing agent, generate free radicals, accelerate the curing speed of the unsaturated resin, increase the crosslinking density of the unsaturated polyester resin, increase the network structure, improve its strength, hardness and toughness, and can also reduce the bubbles and shrinkage holes of the unsaturated polyester resin, reduce surface defects, make the surface smoother and more uniform, and improve the surface gloss.
[0020] Curing agent is a key component in the curing process of unsaturated polyester resin. It can cure the unsaturated double bonds in the resin into a three-dimensional network structure, significantly improving the strength, toughness and durability of the material.
[0021] Flame retardants can enhance the flame resistance and flame retardancy of resin crafts when they come into contact with fire or high temperature environments.
[0022] Defoaming agents can effectively prevent the generation of bubbles during the preparation of resin handicrafts and improve the uniformity and aesthetics of the products.
[0023] Anti-aging agents can delay the aging of polymer compounds, extend the service life of handicrafts, reduce yellowing, cracking, and splitting, and maintain color.
[0024] In a second aspect, the present application provides a process for preparing a resin handicraft, which adopts the following technical solution: A preparation process of a resin handicraft comprises the following steps: The unsaturated polyester resin, filler, defoamer, flame retardant and antioxidant are mixed evenly, and a curing agent, accelerator and peanut oil are added and mixed evenly to prepare a slurry; The slurry is injected into the mold. When the volume of the slurry is 50-90% of the volume of the mold, vacuum is applied for 5-10 minutes, the mold is placed at room temperature for 10-12 hours, the mold is demolded, and the mold is fixed at 90-100°C for 3-4 hours to obtain a crude product. The crude product is polished to obtain a finished resin product.
[0025] By adopting the above technical scheme, unsaturated polyester resin and other raw materials are mixed to prepare slurry, which is injected into the mold, vacuumized, cured at room temperature, and heated to shape after demolding. This can form a tighter three-dimensional network structure between resin molecules, improve the strength and hardness of the handicraft, and eliminate the residual stress caused by temperature, chemical reaction, etc. during the curing process of the handicraft, thereby increasing dimensional stability.
[0026] Optionally, the crude product is polished after the following pretreatment: The epoxy silane coupling agent modified micro-nano cellulose solution is spin-coated on the surface of the crude product, and then cured by ultraviolet light for 100-120s. The preparation method of the epoxy silane coupling agent modified micro-nano cellulose solution is as follows: the epoxy silane coupling agent modified micro-nano cellulose is dispersed in THF to obtain a base solution with a concentration of 20-30wt%, and diphenyl iodine hexafluorophosphate is added. salt, and mixed evenly to obtain epoxy silane coupling agent modified micro-nano cellulose solution, epoxy silane coupling agent modified micro-nano cellulose and diphenyl iodine hexafluorophosphate The mass ratio of salt is 1:0.08-0.1.
[0027] Resin crafts need to be wiped from time to time, otherwise dust will continue to accumulate, especially in some tiny gaps, where dust is difficult to clean and affects the appearance of the crafts. By adopting the above technical solution, micro-nano cellulose is modified using epoxy silane coupling agent, and epoxy groups are grafted on the surface of micro-nano cellulose. The chemical cross-linking reaction between epoxy groups increases the interaction between micro-nano cellulose, thereby increasing the mechanical strength of the resin crafts. Diphenyl iodine hexafluorophosphate is used Salt acts as a UV cationic initiator, causing cross-linking polymerization reactions between epoxy groups, thereby obtaining a transparent, uniform, smooth-surfaced and densely-filled coating through UV curing, which improves the smoothness and density of the surface of the resin handicraft, while enhancing its anti-dust accumulation effect and anti-fouling ability.
[0028] Optionally, the preparation method of the epoxy silane coupling agent modified micro-nano cellulose is: The micro-nano cellulose is added into the aqueous solution of epoxy silane coupling agent, ultrasonicated, filtered and dried, and the mass ratio of the micro-nano cellulose to the epoxy silane coupling agent is 1:0.15-0.35.
[0029] By adopting the above technical scheme, micro-nano cellulose is placed in an aqueous solution of epoxy silane coupling agent so that its surface carries epoxy groups, thereby undergoing cross-linking polymerization under the action of a cationic initiator to form a protective coating of resin crafts on the crude product.
[0030] Optionally, the epoxy silane coupling agent is selected from at least one of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-ureidopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0031] Optionally, the micro-nano cellulose is pretreated as follows: Adding nano zirconium oxide to an aqueous solution of silane coupling agent KH550, ultrasonicating, filtering, and drying to obtain a pretreated product, wherein the mass ratio of nano zirconium oxide to silane coupling agent KH550 is 1:0.1-0.3; The pretreated material is dispersed in deionized water, the pH is adjusted to 13-14, 1,4-butanediol diglycidyl ether is added, and mixed to obtain a treatment solution, wherein the mass ratio of silane coupling agent KH550 to 1,4-butanediol diglycidyl ether is 2:1; The treatment liquid is uniformly sprayed onto the EVOH nanofibers, and dried at 120-130° C. for 1-2 hours to obtain pretreated nanofibers; The micro-nano cellulose is dispersed in deionized water to obtain a dispersion solution with a concentration of 20-30 wt %, and the pretreated nanofibers are repeatedly immersed in the dispersion solution and dried.
[0032] By adopting the above technical solution, KH550 is used to pretreat nano zirconium oxide. The nano zirconium oxide particles have chemical inertness, excellent thermal stability and high hardness. The terminal -NH 2 It has a self-catalytic effect, which is beneficial to react with the hydroxyl groups on the surface of zirconium dioxide particles to form hydrogen bonds and be adsorbed to the surface of nano zirconium dioxide. 1,4-Butanediol diglycidyl ether with a double epoxy group is used as a cross-linking agent. The amino group of KH550 reacts with the epoxy group, thereby realizing the heating cross-linking and curing of nano zirconium oxide on the surface of EVOH nanofibers, thereby forming a zirconium oxide particle film on the EVOH nanofibers; the pretreated EVOH nanofibers are then used as a matrix, and after repeated impregnation and drying, micro-nano cellulose is coated on the pretreated EVOH nanofibers. The use of EVOH nanofibers enhances the tensile and impact resistance of micro-nano cellulose. The use of zirconium oxide particle film increases the interface fastness between EVOH nanofibers and micro-nano cellulose, and at the same time increases the impact resistance of resin handicrafts.
[0033] In summary, this application has the following beneficial effects: 1. Since the present application adopts unsaturated polyester resin, filler, defoamer and peanut oil as raw materials to prepare resin handicrafts, peanut oil can improve the fluidity, flexibility and adhesion of unsaturated polyester resin, so that the slurry can be completely filled into the inner wall of the mold, reducing the generation of tiny pores, improving the surface quality and increasing the anti-aging property of the resin handicrafts.
[0034] 2. In the present application, dipentaerythritol hexaacrylate and epoxy polyacrylate are preferably added to the raw materials of the resin crafts, both of which serve as viscosity modifiers and surfactants to increase the fluidity of the unsaturated polyester resin and reduce the generation of pores.
[0035] 3. In the present application, hydrophobically modified carbon nanotubes are preferably used as fillers, and the hydrophobically modified carbon nanotubes are made of TDI, tetraethyl orthosilicate, etc. TDI can form hydrogen bonds with groups such as hydroxyl groups in carbon nanotubes, thereby improving the compatibility of carbon nanotubes in unsaturated polyester resins. In addition, silicon dioxide is synthesized in situ on carbon nanotubes, and TDI can further improve the hydrophobicity of silicon dioxide. The interaction between silicon dioxide and carbon nanotubes increases the dispersibility of the two, thereby improving the impact resistance and dust accumulation prevention effect of resin handicrafts.
[0036] 4. The method of the present application sprays a solution containing micro-nano cellulose modified by epoxy silane coupling agent on the surface of the crude product, and forms a dense, uniform and smooth coating through UV curing to increase the dustproof effect and drop and crack resistance of the resin handicraft. In addition, the micro-nano cellulose is pretreated with nano-zirconium oxide, EVOH nanofibers, etc. to improve the mechanical strength of the micro-nano cellulose, thereby further improving the drop resistance of the handicraft. DETAILED DESCRIPTION
[0037] The following examples further illustrate the present application in detail.
[0038] Preparation Examples 1-5 of Hydrophobically Modified Carbon Nanotubes Preparation Example 1: 100 g of carbon nanotubes were dispersed in 1000 mL of acetone solution, 200 g of 2,4-toluene diisocyanate was added, stirred at 80° C. for 10 h, filtered, and vacuum dried at room temperature for 24 h to obtain pretreated carbon nanotubes, the carbon nanotubes were selected from Nanjing Xianfeng Nano, model XFM31; The pretreated carbon nanotubes were added to a ethyl orthosilicate solution formed by 100 g ethyl orthosilicate and 1600 g ethanol, and 80 g 25% ammonia water and 80 g ethanol were added, stirred at 60° C. for 3 h, aged, and dried at 200° C. for 12 h.
[0039] Preparation Example 2: 100 g of carbon nanotubes were dispersed in 1000 mL of acetone solution, 300 g of 2,4-toluene diisocyanate was added, stirred at 80° C. for 10 h, filtered, and vacuum dried at room temperature for 24 h to obtain pretreated carbon nanotubes, the carbon nanotubes were selected from Nanjing Xianfeng Nano, model XFM31; The pretreated carbon nanotubes were added to a ethyl orthosilicate solution formed by 150 g ethyl orthosilicate and 1600 g ethanol, and 80 g 25% ammonia water and 80 g ethanol were added, stirred at 60° C. for 3 h, aged, and dried at 200° C. for 12 h.
[0040] Preparation Example 3: Disperse 100 g of carbon nanotubes in 1000 mL of acetone solution, add 200 g of 2,4-toluene diisocyanate, stir at 80° C. for 10 h, filter, and vacuum dry at room temperature for 24 h. The carbon nanotubes are selected from Nanjing Xianfeng Nano, model XFM31.
[0041] Preparation Example 4: Add 100 g of carbon nanotubes to a ethyl orthosilicate solution formed by 100 g of ethyl orthosilicate and 1600 g of ethanol, add 80 g of 25% ammonia water and 80 g of ethanol, stir at 60°C for 3 hours, age, and dry at 200°C for 12 hours. The carbon nanotubes are selected from Nanjing Xianfeng Nano, model XFM31.
[0042] Preparation Example 5: 100 g of carbon nanotubes were dispersed in a mixture of 100 g of hexadecyltrimethylammonium bromide and 800 g of deionized water, stirred at room temperature for 2 h, filtered, and dried at 200° C. for 12 h. The carbon nanotubes were selected from Nanjing Xianfeng Nano, model XFM31.
[0043] Preparation Examples 6-12 of Micro-Nano Cellulose Modified by Epoxy Silane Coupling Agent Preparation Example 6: (1) Preparation of micro-nano cellulose: bamboo fiber powder was sieved through a 100-mesh sieve, treated with a 3 wt % sodium hydroxide solution at 70° C. for 1 h, with a solid-liquid ratio of 1 g / 20 ml, washed until neutral, filtered, and dried; then treated with 10 wt % sulfuric acid at 60° C. for 2 h, with a solid-liquid ratio of 1 g / 20 ml, and diluted with water to terminate the hydrolysis reaction; centrifuged at 100 rpm for 10 min, washed with deionized water until neutral, vacuum dried, and ground to obtain micro-nano cellulose; (2) 100 g of micro-nano cellulose was added to 1000 ml of an aqueous solution containing 15 g of an epoxy silane coupling agent, ultrasonicated at room temperature for 2 h, filtered, and dried at 60 °C for 12 h. The epoxy silane coupling agent was 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0044] Preparation Example 7: (1) Preparation of micro-nano cellulose: bamboo fiber powder was sieved through a 100-mesh sieve, treated with a 3 wt % sodium hydroxide solution at 70° C. for 1 h, with a solid-liquid ratio of 1 g / 20 ml, washed until neutral, filtered, and dried; then treated with 10 wt % sulfuric acid at 60° C. for 2 h, with a solid-liquid ratio of 1 g / 20 ml, and diluted with water to terminate the hydrolysis reaction; centrifuged at 100 rpm for 10 min, washed with deionized water until neutral, vacuum dried, and ground to obtain micro-nano cellulose; (2) 100 g of micro-nano cellulose was added to 1000 ml of an aqueous solution containing 35 g of an epoxy silane coupling agent, ultrasonicated at room temperature for 2 h, filtered, and dried at 60 °C for 12 h. The epoxy silane coupling agent was γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0045] Preparation Example 8: The difference from Preparation Example 6 is that the micro-nano cellulose is pretreated as follows before being added to the aqueous solution of epoxy silane coupling agent: (1) adding 20 g of nano-zirconia to 100 g of an aqueous solution containing 6 g of a silane coupling agent KH550, ultrasonicating at a power of 200 W for 30 min, filtering, and drying at 80° C. for 12 h to obtain a pretreated product; (2) dispersing the pretreated material into 80 g of deionized water, adjusting the pH to 14, adding 1,4-butanediol diglycidyl ether, and mixing evenly to obtain a treated solution, wherein the mass ratio of 1,4-butanediol diglycidyl ether to the silane coupling agent KH550 is 1:2; (3) spraying the treatment liquid evenly onto the EVOH nanofibers, and drying at 130° C. for 1 h to obtain pretreated nanofibers, wherein the spraying amount of the treatment liquid is 15 wt % of the mass of the EVOH nanofibers. The EVOH nanofibers are prepared by vacuum drying EVOH and vinyl acetate butyrate in a mass ratio of 2:8 at 80° C. for 3 h, extruding at 220° C., stretching, and extracting with acetone at 80° C. for 72 h; (4) 30 g of micro-nano cellulose was dispersed in deionized water to obtain a dispersion with a concentration of 30 wt %, and the pretreated nanofibers were immersed in the dispersion for 20 min. After filtering, the dispersion was dried. The immersion and drying were repeated for 5 times.
[0046] Preparation Example 9: The difference from Preparation Example 6 is that the micro-nano cellulose is pretreated as follows before being added to the aqueous solution of epoxy silane coupling agent: (1) adding 20 g of nano-zirconia to 100 g of an aqueous solution containing 2 g of a silane coupling agent KH550, ultrasonicating at a power of 200 W for 30 min, filtering, and drying at 80° C. for 12 h to obtain a pretreated product; (2) dispersing the pretreated material into 80 g of deionized water, adjusting the pH to 13, adding 1,4-butanediol diglycidyl ether, and mixing evenly to obtain a treated solution, wherein the mass ratio of 1,4-butanediol diglycidyl ether to the silane coupling agent KH550 is 1:2; (3) spraying the treatment liquid evenly onto the EVOH nanofibers, and drying at 120°C for 2h to obtain pretreated nanofibers, wherein the spraying amount of the treatment liquid is 15wt% of the mass of the EVOH nanofibers, and the EVOH nanofibers are made by vacuum drying EVOH and vinyl acetate butyrate at a mass ratio of 2:8 at 80°C for 3h, extruding at 220°C, stretching, and extracting with acetone at 80°C for 72h, and the EVOH is selected from Mitsui Polymerization, and the model is EV40W; (4) Dispersing 20 g of micro-nanocellulose into deionized water to obtain a dispersion with a concentration of 20 wt %, immersing the pretreated nanofibers in the dispersion for 20 min, filtering and drying, and repeating the immersion and drying for 5 times.
[0047] Preparation Example 10: The difference from Preparation Example 6 is that the micro-nano cellulose is pretreated as follows before being added to the aqueous solution of epoxy silane coupling agent: 30g of micro-nano cellulose was dispersed in deionized water to obtain a dispersion with a concentration of 30wt%, and EVOH nanofibers were immersed in the dispersion for 20min, filtered and dried, and the immersion and drying were repeated 5 times. EVOH nanofibers were made by vacuum drying EVOH and vinyl acetate butyrate with a mass ratio of 2:8 at 80°C for 3h, extruded at 220°C, stretched, and extracted with acetone at 80°C for 72h. EVOH was selected from Mitsui Polymer, model EV40W.
[0048] Preparation Example 11: Before adding micro-nano cellulose to the aqueous solution of epoxy silane coupling agent, the following pretreatment is performed: Add 20 g of nano zirconium oxide to 80 g of deionized water to obtain a treatment solution; The treatment liquid was sprayed evenly onto the EVOH nanofibers, and dried at 130°C for 1h to obtain pretreated nanofibers. The spraying amount of the treatment liquid was 15wt% of the mass of the EVOH nanofibers. The EVOH nanofibers were made by vacuum drying EVOH and vinyl acetate butyrate at a mass ratio of 2:8 at 80°C for 3h, extruding at 220°C, stretching, and extracting with acetone at 80°C for 72h. The EVOH was selected from Mitsui Polymerization, and the model was EV40W. 30 g of micro-nano cellulose was dispersed in deionized water to obtain a dispersion with a concentration of 30 wt %. The pretreated nanofibers were immersed in the dispersion for 20 min, filtered and dried, and the immersion and drying were repeated 5 times.
[0049] Preparation Example 12: Before adding micro-nano cellulose to the aqueous solution of epoxy silane coupling agent, the following pretreatment is performed: (1) adding 20 g of nano-zirconia to 100 g of an aqueous solution containing 6 g of a silane coupling agent KH550, ultrasonicating at a power of 200 W for 30 min, filtering, and drying at 80° C. for 12 h to obtain a pretreated product; (2) dispersing the pretreated material into 80 g of deionized water, adjusting the pH to 14, adding 1,4-butanediol diglycidyl ether, and mixing evenly to obtain a treated solution, wherein the mass ratio of 1,4-butanediol diglycidyl ether to the silane coupling agent KH550 is 1:2; (3) The treatment liquid is evenly sprayed onto the micro-nanocellulose and dried at 130°C for 1 hour. The spraying amount of the treatment liquid is 15wt% of the mass of the micro-nanocellulose. EVOH nanofibers are made by vacuum drying EVOH and vinyl acetate butyrate in a mass ratio of 2:8 at 80°C for 3 hours, and then extruded and stretched at 220°C and extracted with acetone at 80°C for 72 hours. The EVOH is selected from Mitsui Polymer, model EV40W. Example
[0050] Embodiment 1: A resin handicraft, the raw material dosage is shown in Table 1, in Table 1, the unsaturated polyester resin is selected from Guangzhou Zhanhong Chemical Co., Ltd., the product number is 191A, the filler is stone powder, the curing agent is methyl ethyl ketone peroxide, the defoaming agent is polydimethylsiloxane, the flame retardant is sodium hexametaphosphate, the accelerator is cobalt cyclohexane, and the antioxidant is N,N-diphenyl-p-phenylenediamine.
[0051] The preparation process of the above resin handicraft comprises the following steps: S1. Mix unsaturated polyester resin, filler, defoamer, flame retardant and antioxidant evenly, add curing agent, accelerator and peanut oil, and mix evenly to obtain slurry; S2. Inject the slurry into the mold. When the volume of the slurry is 90% of the volume of the mold, evacuate to -0.08MPa and maintain the pressure for 10 minutes. Place it at room temperature for 12 hours. After demolding, heat it to 100°C at a rate of 5°C / min, fix it at 100°C for 3 hours, cool it to room temperature, and obtain a crude product. Polish the crude product to make it smooth to obtain a resin handicraft.
[0052] Table 1 Amount of raw materials used for resin crafts in Examples 1-7 Example 2: A resin handicraft, the raw material dosage is shown in Table 1, in which the unsaturated polyester resin is selected from Guangzhou Zhanhong Chemical Co., Ltd., the product number is 191A, the filler is stone powder, the curing agent is cyclohexanone peroxide, the defoaming agent is tributyl phosphate, the flame retardant is melamine cyanuric acid, the accelerator is dimethylaniline, and the antioxidant is 2,6-di-tert-butyl-4-diphenol.
[0053] The preparation process of the above resin handicraft comprises the following steps: S1. Mix unsaturated polyester resin, filler, defoamer, flame retardant and antioxidant evenly, add curing agent, accelerator and peanut oil, and mix evenly to obtain slurry; S2. Inject the slurry into the mold. When the volume of the slurry is 70% of the volume of the mold, evacuate to -0.09MPa and maintain the pressure for 8 minutes. Place it at room temperature for 10 hours. After demolding, heat it to 100°C at a rate of 5°C / min, fix it at 90°C for 4 hours, cool it to room temperature, and obtain a crude product. Polish the crude product to make it smooth to obtain a resin handicraft.
[0054] Embodiment 3: A resin handicraft, the raw material dosage is shown in Table 1, in Table 1, the unsaturated polyester resin is selected from Guangzhou Zhanhong Chemical Co., Ltd., the product number is 191A, the filler is stone powder, the curing agent is benzoyl peroxide, the defoaming agent is polydimethylsiloxane, the flame retardant is ammonium dihydrogen phosphate, the accelerator is cobalt cyclohexane, and the antioxidant is triphenyl phosphite.
[0055] The preparation process of the above resin handicraft comprises the following steps: S1. Mix unsaturated polyester resin, filler, defoamer, flame retardant and antioxidant evenly, add curing agent, accelerator and peanut oil, and mix evenly to obtain slurry; S2. Inject the slurry into the mold. When the volume of the slurry is 50% of the volume of the mold, evacuate to -0.07MPa and maintain the pressure for 10 minutes. Place it at room temperature for 12 hours. After demolding, shape it at 100°C for 4 hours to obtain a crude product. Polish the crude product to make a resin handicraft.
[0056] Example 4-5: A resin handicraft, which is different from Example 1 in that the amounts of raw materials are as shown in Table 1, and the preparation methods are different in that S1, unsaturated polyester resin, filler, defoamer, flame retardant, dipentaerythritol hexaacrylate, epoxy polyacrylate and antioxidant are mixed evenly, a curing agent, an accelerator and peanut oil are added, and the mixture is mixed evenly to obtain a slurry, dipentaerythritol hexaacrylate is selected from Zhongshan Dixin Chemical, brand 01, item number WANG1, and epoxy polyacrylate is selected from Shandong Gaotai Chemical Technology, model number 345342.
[0057] Example 6: A resin handicraft. Compared with Example 4, the raw material dosage is as shown in Table 1, and the difference in the preparation method is that S1. Unsaturated polyester resin, filler, defoamer, flame retardant, dipentaerythritol hexaacrylate and antioxidant are mixed evenly, and a curing agent, an accelerator and peanut oil are added, and the mixture is mixed evenly to obtain a slurry.
[0058] Example 7: A resin handicraft, which is different from Example 4 in that the amounts of raw materials are as shown in Table 1, and the difference in the preparation method is that S1, unsaturated polyester resin, filler, defoamer, flame retardant, epoxy polyacrylate and antioxidant are mixed evenly, and a curing agent, accelerator and peanut oil are added, and the mixture is mixed evenly to obtain a slurry.
[0059] Example 8: A resin handicraft, which is different from Example 4 in that the filler is hydrophobically modified carbon nanotubes, and the hydrophobically modified carbon nanotubes are made by Preparation Example 1.
[0060] Example 9: A resin handicraft, which is different from Example 4 in that the filler is hydrophobically modified carbon nanotubes, and the hydrophobically modified carbon nanotubes are made by Preparation Example 2.
[0061] Example 10: A resin handicraft, which is different from Example 8 in that the hydrophobically modified carbon nanotubes are made from Preparation Example 3.
[0062] Example 11: A resin handicraft, which is different from Example 8 in that the hydrophobically modified carbon nanotubes are made from Preparation Example 4.
[0063] Example 12: A resin handicraft, which is different from Example 8 in that the hydrophobically modified carbon nanotubes are made from Preparation Example 5.
[0064] Embodiment 13: A resin handicraft, which differs from Embodiment 8 in that, in step S2, the rough product is subjected to the following pretreatment before polishing: The surface of the crude product was spin-coated with an epoxy silane coupling agent-modified micro-nano cellulose solution at a speed of 1000 rpm, and then cured with 180 W ultraviolet light for 120 s. The spin-coating amount was 10 wt % of the crude product quality. The preparation method of the epoxy silane coupling agent-modified micro-nano cellulose solution is as follows: 20g of epoxysilane coupling agent modified micro-nanocellulose was dispersed in THF to obtain a base solution with a concentration of 20wt%, and diphenyliodonium hexafluorophosphate was added. salt, and mixed evenly to obtain epoxy silane coupling agent modified micro-nano cellulose solution, epoxy silane coupling agent modified micro-nano cellulose and diphenyl iodine hexafluorophosphate The mass ratio of the salt is 1:0.1, and the epoxy silane coupling agent-modified micro-nano cellulose is prepared according to Preparation Example 6.
[0065] Embodiment 14: A resin handicraft, which differs from Embodiment 8 in that, in step S2, the rough product is subjected to the following pretreatment before polishing: The epoxy silane coupling agent modified micro-nano cellulose solution was spin-coated on the surface of the crude product at a speed of 1000 rpm, and then cured by 180 W ultraviolet light for 100 s. The spin-coating amount was 10 wt % of the crude product quality. The preparation method of the epoxy silane coupling agent modified micro-nano cellulose solution is as follows: 30 g of epoxysilane coupling agent-modified micro-nanocellulose was dispersed in THF to obtain a base solution with a concentration of 30 wt %. Diphenyl iodonium hexafluorophosphate was added. salt, and mixed evenly to obtain epoxy silane coupling agent modified micro-nano cellulose solution, epoxy silane coupling agent modified micro-nano cellulose and diphenyl iodine hexafluorophosphate The mass ratio of the salt is 1:0.08, and the epoxy silane coupling agent-modified micro-nano cellulose is prepared according to Preparation Example 7.
[0066] Example 15: A resin handicraft, which is different from Example 13 in that the epoxy silane coupling agent-modified micro-nano cellulose is made from Preparation Example 8.
[0067] Example 16: A resin handicraft, which is different from Example 13 in that the epoxy silane coupling agent-modified micro-nano cellulose is made from Preparation Example 9.
[0068] Example 17: A resin handicraft, which is different from Example 15 in that the epoxy silane coupling agent-modified micro-nano cellulose is made from Preparation Example 10.
[0069] Example 18: A resin handicraft, which is different from Example 15 in that the epoxy silane coupling agent-modified micro-nano cellulose is made from Preparation Example 11.
[0070] Example 19: A resin handicraft, which is different from Example 15 in that the epoxy silane coupling agent-modified micro-nano cellulose is made from Preparation Example 12.
[0071] Comparative Example Comparative Example 1: A resin handicraft, which is different from Example 1 in that peanut oil is not added.
[0072] Comparative Example 2: A resin handicraft, which differs from Example 1 in that an equal amount of palm oil is used instead of peanut oil.
[0073] Comparative Example 3: A resin handicraft, which is different from Example 1 in that it only contains 100g of unsaturated polyester resin and 1300g of stone powder.
[0074] Performance testing Resin crafts were prepared according to the methods in the examples and comparative examples, and performance tests were performed according to the following methods. The test results are recorded in Table 2.
[0075] 1. Impact strength: Test in accordance with GB / T14153-1993 "General rules for drop weight impact test methods for rigid plastics".
[0076] 2. Tensile strength: Test in accordance with GB / T1040-1992 "Test method for tensile properties of plastics".
[0077] 3. Anti-dust accumulation effect: prepare a sample with a volume of 25cm×25cm×25cm, use a fan to blow dust to the surface of the sample at the same time, stop blowing after 30 minutes, collect the amount of dust on the surface of each sample, and calculate the anti-dust accumulation rate based on the amount of dust M1 collected on the surface of the sample in comparative example 3 and the amount of dust M2 collected on the surface of the samples in other groups according to the following formula: W=M2 / M1×100%, when W value is less than 50%, it is recorded as qualified, when W value is 10-30%, it is recorded as good, and when W value is less than 10%, it is recorded as excellent.
[0078] 4. Number of pores: A cylindrical specimen with a volume of 130 mm in length in the straight axis direction and a diameter of 10 mm was prepared, and the number and diameter of the pores were observed using a digital microscope (manufactured by KEYENCE: VHX-500, observation magnification: 100 times). The observation range was 2 cm×2 cm. One sample was taken for observation in each embodiment, but each sample was observed at 5 locations. The average number of pores at the 5 observation points was calculated, and the average diameter of the pores at the 5 observation points was calculated.
[0079] Table 2 Performance test results of resin crafts Combining the raw materials of Examples 1-3 and the data in Table 2, it can be seen that the resin handicrafts obtained by mixing unsaturated polyester resin with stone powder, defoaming agent and other components for casting and vacuuming have strong impact resistance and crack resistance, less bubbles and small pore diameters, less surface dust accumulation and good dust prevention effect compared with the basic model containing only unsaturated resin and stone powder.
[0080] Compared with Example 1, Example 4-5 also uses dipentaerythritol hexaacrylate and epoxy polyacrylate in the resin crafts. The data in Table 2 show that the number of surface pores of the resin crafts prepared in Example 4-5 is reduced, the average pore diameter is reduced, and the surface density of the crafts is increased.
[0081] Compared with Example 4, no epoxy polyacrylate was added in Example 6, and dipentaerythritol hexaenoate was used instead of epoxy polyacrylate in Example 7. The data in Table 2 show that the number of pores on the surface of the resin crafts prepared in Examples 6 and 7 is reduced, the pore diameter is reduced, and the surface density is further increased.
[0082] In Example 8 and Example 9, the hydrophobically modified carbon nanotubes prepared in Preparation Example 1 and Preparation Example 2 were used as fillers, respectively. Compared with Example 4, the impact strength of the resin crafts was significantly improved, the drop resistance was enhanced, the amount of dust accumulation on the surface was reduced, and the dust-proof effect was improved.
[0083] Compared with Example 8, Example 10 is a hydrophobically modified carbon nanotube made of carbon nanotubes and TDI, without adding ethyl orthosilicate, etc. As shown in Table 2, the impact strength of the resin craft prepared in Example 10 decreases, the crack resistance weakens, and the number of pores increases slightly.
[0084] In Example 11, the hydrophobically modified carbon nanotubes prepared in Preparation Example 4 were used. Compared with Example 8, 2,4-toluene diisocyanate was not used, and silica was loaded on the carbon nanotubes. It can be seen that the amount of dust on the surface of the resin handicraft prepared in Example 11 increased, the number of pores did not change significantly, the impact strength decreased slightly, and the drop resistance was weakened.
[0085] In Example 12, the carbon nanotubes prepared in Preparation Example 5 were hydrophobically modified using hexadecyltrimethylammonium bromide. Table 2 shows that compared with Example 8, the impact resistance decreased, the crack resistance weakened, and the porosity increased slightly, but the amount of dust accumulation on the surface was not much different from that in Example 8.
[0086] Compared with Example 8, Example 13 and Example 14 are also sprayed with a solution containing epoxy silane coupling agent modified micro-nano cellulose on the product surface, and the epoxy silane coupling agent modified micro-nano cellulose is prepared by Preparation Example 6 and Preparation Example 7, respectively, and the coating is obtained by UV curing. Table 2 shows that the resin handicrafts prepared in Example 13 and Example 14 have less surface dust accumulation, improved impact strength, and increased surface density.
[0087] Compared with Example 13, Example 15 and Example 6 are prepared from Preparation Example 8 and Preparation Example 9, respectively. Compared with Preparation Example 6, Preparation Example 8 and Preparation Example 9 also pre-treat the micro-nano cellulose. Table 2 shows that the resin crafts prepared in Example 15 and Example 16 have increased impact resistance, enhanced crack resistance, reduced surface dust accumulation, and increased dustproof effect.
[0088] In Example 17, the epoxy silane coupling agent prepared in Preparation Example 10 was used to modify the micro-nano cellulose. Compared with Example 15, the treatment liquid containing nano zirconium oxide was not sprayed on the EVOH nanofibers. It can be seen that the impact strength of the resin handicraft is reduced, the amount of dust accumulation on the surface is increased, and the dust-proof effect is weakened.
[0089] Compared with Example 15, Example 18 uses the epoxy silane coupling agent prepared in Preparation Example 11 to modify the micro-nano cellulose, wherein unpretreated zirconium oxide is used. The data in Table 2 show that the impact resistance of the resin craft prepared in Example 18 is slightly reduced, and the amount of dust accumulation on the surface is increased.
[0090] In Example 19, the epoxy silane coupling agent prepared in Preparation Example 12 was used to modify the micro-nano cellulose. Compared with Example 15, zirconium oxide was treated and then sprayed on the micro-nano cellulose. Table 2 shows that the tensile resistance of the resin crafts prepared in Example 19 decreased and the crack resistance was weakened.
[0091] In Comparative Example 1, peanut oil was not added. Compared with Example 1, the number of pores on the surface of the resin craft made in Comparative Example 1 increased significantly, and the pore diameter increased.
[0092] In Comparative Example 2, palm oil was used instead of peanut oil. Table 2 shows that, compared with Example 1, the impact resistance, tensile resistance, dust resistance and surface density of the resin crafts prepared by replacing peanut oil with palm oil were reduced.
[0093] Compared with Example 1, in Comparative Example 3, only unsaturated polyester resin and stone powder are used as raw materials. After mixing, injection and vacuuming, the obtained resin handicraft has more pores on the surface, and the pore diameter is larger, and the aesthetics is reduced.
[0094] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A resin handicraft, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of unsaturated polyester resin, 0-1300 parts of filler, 1-3 parts of peanut oil, 0.5-3 parts of curing agent, 0.3-3 parts of defoaming agent, 0.5-1.5 parts of flame retardant, 0.5-1 parts of accelerator and 0.1-1.5 parts of antioxidant.
2. The resin handicraft according to claim 1, characterized in that: The resin crafts are further added with 1-2 parts by weight and 0.5-1 parts by weight of epoxy polyacrylate.
3. The resin handicraft according to claim 1, characterized in that: The filler is hydrophobically modified carbon nanotubes.
4. The resin handicraft according to claim 3, characterized in that: The method for preparing the hydrophobically modified carbon nanotubes is as follows: dispersing the carbon nanotubes in an acetone solution, adding 2,4-toluene diisocyanate, stirring for 8-10 hours, filtering, and vacuum drying to obtain pretreated carbon nanotubes; The pretreated carbon nanotubes are placed in a tetraethyl orthosilicate solution, and ammonia water and ethanol are added, stirred at 60-65° C. for 3-5 hours, aged, and then dried at 190-200° C. for 2-3 hours.
5. The resin handicraft according to claim 4, characterized in that: The mass ratio of the carbon nanotube, 2,4-toluene diisocyanate and tetraethyl orthosilicate is 1:2-3:1-1.
5.
6. The resin handicraft according to claim 1, characterized in that: The accelerator is at least one of cobalt naphthenate, dimethylaniline, cobalt naphthenate and cobalt octanoate; The curing agent is at least one of methyl ethyl ketone peroxide, cyclohexanone peroxide, hydrogen peroxide, peroxydicarbonate and benzoyl peroxide; The flame retardant is selected from at least one of sodium hexametaphosphate, ammonium polyphosphate, ammonium dihydrogen phosphate, diphenyl xylene phosphate, trisnonyl phosphite, triisopropyl phosphate, trimethyl phosphonate, dimethyl methylphosphonate, melamine, melamine cyanuric acid, and melamine phosphate; The defoaming agent is selected from at least one of polydimethylsiloxane, tributyl phosphate, polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether, polyoxypropylene glycerol ether and polyacrylamide; The antioxidant is selected from at least one of N,N-diphenyl-p-phenylenediamine, 2-thiol benzoimidazole, 2,6-di-tert-butyl-4-methylphenol, triphenyl phosphite and tributyl sulfite.
7. The process for preparing the resin handicraft according to any one of claims 1 to 6, characterized in that: The following steps are involved: The unsaturated polyester resin, filler, defoamer, flame retardant and antioxidant are mixed evenly, and a curing agent, accelerator and peanut oil are added and mixed evenly to prepare a slurry; The slurry is injected into the mold. When the volume of the slurry is 50-90% of the volume of the mold, vacuum is applied for 5-10 minutes, and the mold is placed at room temperature for 10-12 hours. The mold is demolded and shaped at 90-100°C for 3-4 hours to obtain a crude product. The crude product is polished to make a finished resin product.
8. The process for preparing the resin handicraft according to claim 7, characterized in that: The crude product is polished after the following pretreatment: The epoxy silane coupling agent modified micro-nano cellulose solution is spin-coated on the surface of the crude product, and then cured by ultraviolet light for 100-120s. The preparation method of the epoxy silane coupling agent modified micro-nano cellulose solution is as follows: the epoxy silane coupling agent modified micro-nano cellulose is dispersed in THF to obtain a base liquid with a concentration of 20-30wt%, diphenyliodonium hexafluorophosphate is added, and mixed evenly to obtain the epoxy silane coupling agent modified micro-nano cellulose solution, and the mass ratio of the epoxy silane coupling agent modified micro-nano cellulose and the diphenyliodonium hexafluorophosphate is 1:0.08-0.
1.
9. The process for preparing the resin handicraft according to claim 8, characterized in that: Preparation method of epoxy silane coupling agent modified micro-nano cellulose: The micro-nano cellulose is added into the aqueous solution of epoxy silane coupling agent, ultrasonicated, filtered and dried, and the mass ratio of the micro-nano cellulose to the epoxy silane coupling agent is 1:0.15-0.
35.
10. The resin handicraft according to claim 9, characterized in that: The micro-nano cellulose is pretreated as follows: Adding nano zirconium oxide to an aqueous solution of silane coupling agent KH550, ultrasonicating, filtering, and drying to obtain a pretreated product, wherein the mass ratio of nano zirconium oxide to silane coupling agent KH550 is 1:0.1-0.3; The pretreated material is dispersed in deionized water, the pH is adjusted to 13-14, 1,4-butanediol diglycidyl ether is added, and mixed to obtain a treatment solution, wherein the mass ratio of silane coupling agent KH550 to 1,4-butanediol diglycidyl ether is 2:1; The treatment liquid is uniformly sprayed onto the EVOH nanofibers, and dried at 120-130° C. for 1-2 hours to obtain pretreated nanofibers; The micro-nano cellulose is dispersed in deionized water to obtain a dispersion solution with a concentration of 20-30 wt %, and the pretreated nanofibers are repeatedly immersed in the dispersion solution and dried.
